Surgical aspects in the treatment of Eagle’s Syndrome (Research, Society and Development, 2022)
The styloid process is a bony structure that projects downwards and forwards of the face, being in an anterior position to the Temporal bone, and with a thin and pointed characteristic. Eagle’s syndrome occurs as a result of elongation of the styloid process, after ossification of an embryological remnant of the cartilage of the second branchial arch, or due to calcification of the stylohyoid ligament. The present work aims to discuss the possible forms of surgical treatment for Eagle’s Syndrome, and it is a literature review, carried out from scientific publications in databases such as the Virtual Health Library (VHL), Pubmed/Medline, Scielo and Google Scholar, using descriptors in Portuguese and English. For the treatment of Eagle's Syndrome, the severity of the symptoms is considered, so, in cases of mild to moderate pain, the initial treatment is pharmacological treatment, with administration of antidepressants, benzodiazepines, anticonvulsants or steroid injections and/or local anesthetics. However, in cases of intense and severe pain, the proposed treatment is complete surgical resection of the styloid process (styloidectomy), which can be performed intraorally or extraorally, in which the choice of one of the two will be based on the surgeon's experience and the working conditions. Thus, it is concluded that the choice of treatment depends on a thorough evaluation made by the dentist and the patient's condition.